Analisis Klasifikasi Mitos dalam Tradisi Lisan Masyarakat Lampung - Margaretha, Risma (FKIP Universitas Lampung, 2017)
This study begins from the growing myth as oral traditions in Lampung society. The purpose of this study was to analyze the character of the myth and see relationships in social and cultural life of lampung society. Then to determine myth as marker or the identity of lampung society. The method used in this research is a survey research methods and analyzed with the approach of meaning. It obtained in this study is a myth based on indigenous territories categorizing people who live and believed to Papadun and Saibatin. Myth is closely related to social and cultural life of Lampung society. In myth found values that characterize Lampung society as firm on the establishment, willing to die for the sake of self-esteem, and open to others. Key Word: mite, social cultural, identity, lampung societyDOI: http://dx.doi.org/10.23960/jpp.v7.i2.201701